Nitric Oxide-Sensitive Pulmonary Hypertension in Congenital Rubella Syndrome - Francesco Raimondi; Fiorella Migliaro; Elisa Di Pietro; Francesco Borgia; Antonio Rapacciuolo; Letizia Capasso (Case Reports in Critical Care)
Persistent pulmonary hypertension is a very rare presentation of congenital virus infection. We discuss the case of complete congenital rubella syndrome presenting at echocardiography with pulmonary hypertension that worsened after ductus ligation. Cardiac catheterization showed a normal pulmonary valve and vascular tree but a PAP=40 mmHg. The infant promptly responded to inhaled nitric oxide while on mechanical ventilation and was later shifted to oral sildenafil. It is not clear whether our observation may be due to direct viral damage to the endothelium or to the rubella virus increasing the vascular tone via a metabolic derangement.